Internet search data with spatiotemporal analysis in infectious disease surveillance: Challenges and perspectives - Sun, Hua; Zhang, Yuzhou; Gao, Guang; Wu, Dun (Frontiers in Public Health, 2022)
With the rapid development of internet, the application of internet search data has been seen as a novel data source to offer timely infectious diseases surveillance intelligence. Moreover, the advancements in internet search data, which includes rich information at both space and time scale enable investigators sufficiently consider the spatiotemporal uncertainty, which can benefit researchers to better monitor infectious diseases epidemics. In the study, we provide the necessary groundwork and critical appraisal of the use of internet search data and spatio-temporal analysis approaches by updating current stage of knowledge on them in infectious diseases surveillance. This study also provides the future directions to researchers to investigate the combination of internet search data with spatio-temporal analysis in infectious diseases surveillance. Internet search data demonstrates a promising potential to offer timely epidemic intelligence, which can be seen as the prerequisite for improving infectious diseases surveillance.